2021
DOI: 10.1016/j.cropro.2020.105384
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of early-generation tropical maize testcrosses for grain-yield potential and weevil (Sitophilus zeamais Motschulsky) resistance

Abstract: Smallholder maize farmers in Africa experience pre- and post-harvest production stresses either individually or in combination at different stages of the crop cycle. The maize weevil is among the major post-harvest storage pests. A strategy to address this problem is to develop and promote high yielding maize germplasm with resistance to multiple stresses. A study was conducted to: 1) assess yield and agronomic performance of testcross hybrids developed from early generation lines; and 2) assess the response o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
(66 reference statements)
0
1
0
1
Order By: Relevance
“…A ausência de alguns fatores relacionados ao nível de resistência ao pericarpo, a natureza física e química da película dos grãos, a presença de aleloquímicos, substâncias fenólicas, amido e proteína, podem ter influenciado numa maior suscetibilidade desses genótipos (RASHID et al, 2021;SSERUMAGA et al, 2021;FRAZÃO et al, 2018;NHAMUCHO et al, 2017;VI et al, 2017). Além disso, se proteínas, amido e minerais permitem que insetos possam ter um maior sucesso no ataque de milho, compostos como fibra bruta, ácido fenólico, inibidores de tripsina e de amilase, podem conferir resistência a S. zeamais (NWOSU, 2015).…”
Section: Discussionunclassified
“…A ausência de alguns fatores relacionados ao nível de resistência ao pericarpo, a natureza física e química da película dos grãos, a presença de aleloquímicos, substâncias fenólicas, amido e proteína, podem ter influenciado numa maior suscetibilidade desses genótipos (RASHID et al, 2021;SSERUMAGA et al, 2021;FRAZÃO et al, 2018;NHAMUCHO et al, 2017;VI et al, 2017). Além disso, se proteínas, amido e minerais permitem que insetos possam ter um maior sucesso no ataque de milho, compostos como fibra bruta, ácido fenólico, inibidores de tripsina e de amilase, podem conferir resistência a S. zeamais (NWOSU, 2015).…”
Section: Discussionunclassified
“…The differences in the number of F 1 weevils developed showed that maize weevil attack susceptibility varied among the varieties. Varieties with the highest number of F 1 -progeny had the greatest susceptibility to maize weevil attack, and this may have been due to a lack of resistance mechanisms in the maize grain (Sserumaga et al, 2021).…”
Section: Mortality In S Zeamais F 1 Progeny Emergence and Median Deve...mentioning
confidence: 99%